Value creation in strategic alliance: case study of the Kenya Construction Industry - Nzioka, Christopher Mutunga (Strathmore University, 2019)
A construction sector product needs to create an added value to its clients. Despite its critical importance in the country, the construction industry has continued to face a lot of challenges that have hindered its growth as well as full potential exploitation and benefit enjoyment. This study sought to address this problem by assessing value creation in strategic alliances in the Kenya Construction Industry. Specifically, the study sought to identify strategic alliances adopted in the Kenya Construction industry, the factors that determine the success or failure of strategic alliances and to assess value creation in strategic alliances in the Kenya Construction Industry. The study was grounded on the resource dependence theory, the porter's value chain model and Knowledge Accessing Theory of Strategic Alliances. Descriptive research design was adopted and primary data collected using a questionnaire. Data analysis involved the use of descriptive statistics (frequencies, mean and standard deviation) and inferential statistics (correlation analysis) and the results were presented in form of tables and figures. The study findings indicated that firms in the construction industry had adopted various strategic alliances which included mergers, associations and joint ventures. The study also 'found that the foundation of-strategic alliances success is mainly due to factors amongst them trust, commitment, top management input, coordination and communication, clarity -of objectives and goals, monitoring and evaluation policies and defined roles and responsibilities of each party involved in the alliances. Further, the study found that projects under strategic alliances did perform well which was an indication of value creation. This was because most firms reported having been able to run the projects at the projected costs, being timely, meeting the quality requirements and satisfying their customers. Finally, findings revealed that the value creation benefits of strategic alliances included technology uptake that is exposure to technically advanced technology and acquiring faster ways of service delivery, skills and competence such as acquiring new and improved skills, expertise which comes about through improved ways of handling issues and new experiences which enhanced eligibility and quality services such as improved systems and methods for quality assurance, increased customer satisfaction and better reputation. Thus, the study concluded that undertaking projects in strategic alliances lead to value creation in the construction industry. The study recommended regulation authorities in the Kenyan Construction to propose a policy that would encourage formation of strategic alliances by firms undertaking projects. Further, firms that have adopted alliances or who intend to form alliances were also recommended to formulate clear objectives and goals of the alliances, clarify the roles and responsibilities of each party, to formulate monitoring and evaluation policies and adopt effective channels of communication at the formation stage of the alliances to counter the any challenges that may arise during the execution of the projects.
A Thesis submitted in partial fulfillment of the requirements for the award of the Degree of Masters of Business Administration at Strathmore University Business School
Keywords: Value creation; Strategic alliance; Kenya Construction Industry